Exercise Intensity and Technical Demands of Small-Sided Soccer Games for Under-12 and Under-14 Players: Effect of Area per Player. Issue 6 (June 2017) - Martone, Domenico; Giacobbe, Moreno; Capobianco, Adriano; Imperlini, Esther; Mancini, Annamaria; Capasso, Mario; Buono, Pasqualina; Orrù, Stefania
Abstract : Abstract: Martone, D, Giacobbe, M, Capobianco, A, Imperlini, E, Mancini, A, Capasso, M, Buono, P, and Orrù, S. Exercise intensity and technical demands of small-sided soccer games for under-12 and under-14 players: Effect of area per player. J Strength Cond Res 31(6): 1486–1492, 2017—The aim of this study was to evaluate the effects of 6 different areas per player (AP ) on exercise intensity (EI) measured during small-sided games (SSGs) and expressed as percentage of maximal heart rate (%MHR) and technical actions (TAs) involvement with the ball, crosses, headers, tackles, shots on goal, dribbling, passing, and target passing-in U-12 and U-14 soccer players during SSGs. Seventeen male U-12 soccer players (age 10.0 ± 0.5 years, body mass 39.3 ± 5.3 kg, and height 143.8 ± 4.6 cm) and 16 male U-14 soccer players (age 13.2 ± 0.3 years, body mass 46.6 ± 11.9 kg, and height 154.8 ± 8.5 cm) performed SSGs with different AP : 40, 50, 66.7, 90, 112.5, and 150 m 2 . Our results indicate that at larger AP, the U-12 group's mean EI values were significantly higher than those at smaller AP ( p ⩽ 0.05); in addition, intergroup comparison showed that EI was higher in U-12 than that in U-14 players when AP of 112.5 and 150 m 2 were considered ( p ⩽ 0.05). Technical action analysis evidenced that moving from smaller to larger AP, U-14 players adapted better to AP changes. In conclusion, these results suggest that AP influences differently EI and TAs in U-12 and U-14 players. Our results could be taken into account by conditioning coaches to better tailor the physiological and technical training in young players through the modulation of AP .